High‐Resolution N6‐Methyladenosine (m6A) Map Using Photo‐Crosslinking‐Assisted m6A Sequencing1. (9th December 2014) - Chen, Kai; Lu, Zhike; Wang, Xiao; Fu, Ye; Luo, Guan‐Zheng; Liu, Nian; Han, Dali; Dominissini, Dan; Dai, Qing; Pan, Tao; He, Chuan
Abstract N6‐methyladenosine (m6A) is an abundant internal modification in eukaryotic mRNA and plays regulatory roles in mRNA metabolism. However, methods to precisely locate the m6A modification remain limited. We present here a photo‐crosslinking‐assisted m6A sequencing strategy (PA‐m6A‐seq) to more accurately define sites with m6A modification. Using this strategy, we obtained a high‐resolution map of m6A in a human transcriptome. The map resembles the general distribution pattern observed previously, and reveals new m6A sites at base resolution. Our results provide insight into the relationship between the methylation regions and the binding sites of RNA‐binding proteins.